The relationship between the characteristics of innovation towards the effectiveness of ICT in Malaysia Productivity Corporation - Mohd Hisham Hatimtai,; Hanum Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aims to investigate the relationship of innovation characteristics and demographic factors on the effectiveness of information and communication technology (ICT) utilization in Malaysian Productivity Corporation (MPC). The specific objective of this study is to understand the relationship between innovation characteristics and demographic factors in influencing the level of innovation adoption and which factors are most dominant in influencing the effectiveness of ICT. Using purposive sampling, a total of 210 respondents was selected consisting of MPC headquarters and 5 MPC branches throughout Malaysia. Data and information were collected using questionnaires. Quantitative data were analyzed using Pearson correlation statistical analysis, t-test and ANOVA. The findings showed that there is a significant relationship between innovation characteristics such as relative advantages, compatibility, complexity, observability and triability with the effectiveness of ICT in MPC. Observability has been identified as the major factor with the effectiveness of ICT in MPC with variants of 49%. The results of the analysis also proved that there is no significant difference between demographic factors with the effectiveness of ICT. The result also showed that age and level of academic is not a factor affecting the use of ICT in MPC. This has been proven by the findings of this study that the majority of respondents used ICT between 5 to 7 hours a day and 131 respondents has over 9 years of experience using computer at MPC. This finding suggests that innovation characteristics influenced the acceptance of innovation and will be the determinants of quality in an organization.